2010
DOI: 10.1002/jmv.21841
|View full text |Cite
|
Sign up to set email alerts
|

Molecular detection of adeno‐associated virus in cases of spontaneous and intentional human abortion

Abstract: Pregnancy failure is a common event and often of unknown cause. Some viruses are thought to cause abortions including the adeno-associated viruses (AAV), viruses which are regarded as being without any definitive association to any human disease. This study investigated AAV infection in 81 human abortions, both spontaneous and intentional that occurred up to the 23rd week of gestation. Nucleic acid of AAV-2, 3, and 5 types from 118 decidual and chorionic tissues, collected from the patients in this study, was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…In another study ( Pereira, 2010 ), the presence of AAV was examined in 81 patients, divided into three groups: 13 medically induced abortions, 29 miscarriages and 39 ‘undetermined’ (including 66 decidua and 52 ovarian biopsies from the same patients). AAV DNA was detected in 23/81 (28.4%) of cases for at least one of the decidual or ovular fragments.…”
Section: Resultsmentioning
confidence: 99%
“…In another study ( Pereira, 2010 ), the presence of AAV was examined in 81 patients, divided into three groups: 13 medically induced abortions, 29 miscarriages and 39 ‘undetermined’ (including 66 decidua and 52 ovarian biopsies from the same patients). AAV DNA was detected in 23/81 (28.4%) of cases for at least one of the decidual or ovular fragments.…”
Section: Resultsmentioning
confidence: 99%
“…They detected AAV-2 DNA in the decidual and trophoblastic cells in cases of abortion and noticed that this virus could threaten the pregnancy. 4 Kiehl et al detected AAV DNA in 11 (73%) of 15 trophoblast samples from spontaneous abortion, indicating the possible role of AAV in miscarriage. 56 Matovina et al have not detected AAV DNA in placental specimens; therefore, their findings did not support the role of this virus in miscarriage during the first trimester of pregnancy.…”
Section: Adeno-associated Virus (Aav)mentioning
confidence: 99%
“…However, second trimester miscarriages (14-22 weeks' gestation) rarely occur in 1%-2% of all pregnancies. 4 Miscarriage can also be divided into sub-clinical and clinical. A sub-clinical miscarriage occurs before the woman realizes that she is pregnant, while a clinical miscarriage is the one that is clinically detected.…”
Section: Introductionmentioning
confidence: 99%
“…AAV serotype 2 and many other serotypes are prevalent in human populations worldwide and up to 80% of adult humans have been infected with AAV in their childhood (Boutin et al, 2010;Calcedo et al, 2009;Erles et al, 1999). AAV is generally considered as a nonpathogenic virus, and clinical relevance of AAV infection in humans appears to be limited to male infertility (Erles et al, 2001), early miscarriage in pregnant women (Burguete et al, 1999;Pereira et al, 2010) and protection against cervical cancer (Su & Wu, 1996;Walz & Schlehofer, 1992) although some studies have shown negative results (Strickler et al, 1999). The current relevance of AAV in biological and medical research primarily stems from its benefits as a tool for gene delivery and genetic engineering of the cellular genome and as a refined agent for inducing DDR without damaging the cellular genome (Table 1).…”
Section: Adeno-associated Virus (Aav)mentioning
confidence: 99%